The Influence of GIZTING Video Media on The Knowledge and Behavior of Stunting Toddler Families - Anjani, Amelia Sarah; Adillah, Izzah Kholidatul; Dhuha, Mala Intanin; Wardani, Novita Ika (Journal of Midwifery Science: Basic and Applied Research, 2022)
Background: The incidence of short toddlers or commonly referred to as stunting is a chronic nutritional problem because of malnutrition that has accumulated over a long period of time. Chronic malnutrition occurs from infancy in the womb until the age of two. Data on the prevalence of stunting under five collected by the World Health Organization (WHO) shows that Indonesia is included in the third country with the highest prevalence in the Southeast Asia region / South-East Asia Regional (SEAR). Currently the most important thing to reduce the risk of stunting in toddlers is to provide health education to parents through Video GIZTING, where parents with low education generally trigger stunting in children twice as high as parents with higher education.Objective: To give influence of video media "GIZTING" on knowledge and behavior families of stunting toddlers.Method: This study used a method Quasy experimental with two groups of pre-test post-test design with control and methods of data collection with repeated measurements (pre-test-post-test field trial). Data analysis: Data analysis using computer-assisted SPSS 16 statistical test using independent t test and dependent t test. The results are accepted if p <0.05.Results: The results showed that the difference in the increase in the average score of knowledge, attitudes and behavior of mothers with stunting toddlers after being given stunting prevention education in the stunting video media group and the control group was knowledge of attitudes and behavior. The results of the statistical test of knowledge with p-value = 0.0001 attitude with p-value = 0.0001 and behavior with p-value = 0.0001Conclusion: There was a significant difference between the video gizting media group and the control group after being given education. It is hoped that health education training will be held using video gizting media for mothers with stunting toddlers in increasing knowledge, attitudes and behavior about stunting and one of the efforts to reduce stunting incidence in toddlers.